Деякі аспекти зловживання правом у цивільному та господарському судочинстві - Гуртова, К. М.; Hurtova, K. M.; Ксенія Гуртова (Право і безпека. - 2024. - № 1 (92). - С. 23-30, 2024)
Надано аналіз зловживань процесуальними правами в цивільному та господарському судочинстві. Встановлено, що зловживання процесуальними правами полягає в тому, що одна зі сторін спору, якій формально належать певні права, неправомірно їх реалізує, порушуючи міру і вид поведінки, визначені процесуальним законом, користуючись при цьому тим, що зазначені права об’єктивно не можуть бути чітко окреслені за допомогою прямих заборон. Інакше кажучи, сторони спору при реалізації своїх прав не враховують усі фактичні обставини та не зважають на можливу шкоду для інтересів одна одної. Звернено увагу на те, що різноманітність процесуальних прав у цивільному та господарському судочинстві породжує відповідну кількість видів зловживань ними з боку учасників справи.

The article is devoted to the analysis of abuse of procedural rights in civil and economic proceedings. The views and approaches to the problem of abuse of rights available in the legal literature are considered. Based on the review of scientific literature, the conclusion has been made that there are two general theoretical constructs for understanding the concept of “abuse of procedural rights” within the framework of two approaches. The first approach involves the definition of abuse of procedural rights as misuse of procedural rights, and the second approach – as a type of procedural offence. The article analyses the national legislation on the subject matter of the study. It is argued that the abuse of procedural rights is a certain situation which participants to court proceedings find themselves in, whose rights are violated and are directly related to the rights of the person who abuses them. The exercise of procedural rights is carried out by one party to the dispute within certain limits, as long as it does not contradict the interests of the other party. Violation of these limits leads to the emergence and existence of such a legal phenomenon as abuse of rights. It is established that abuse of procedural rights means that one of the parties to a dispute, which formally has certain rights, unlawfully exercises them, violating the extent and type of behaviour defined by the procedural law, while taking advantage of the fact that these rights cannot be objectively clearly defined by means of direct prohibitions. In other words, when exercising their rights, the parties to the dispute do not take into account all the actual circumstances and do not take into account the possible harm to each other’s interests. Attention is drawn to the fact that the diversity of procedural rights in civil and commercial proceedings gives rise to a corresponding number of types of their abuse by the parties to a case. Due to the absence of a clear list in current legislation of the types of abuse of procedural rights and the existence of certain judicial practice in resolving this category of cases, it should be noted that there are various classifications by scholars.

Представлен анализ злоупотреблений процессуальными правами в гражданском и хозяйственном судопроизводстве. Установлено, что злоупотребление процессуальными правами состоит в том, что одна из сторон спора, которой формально принадлежат определенные права, неправомерно их реализует, нарушая меру и вид поведения, определенные процессуальным законом, пользуясь тем, что указанные права объективно не могут быть четко очерчены с помощью прямых запретов. Иными словами, стороны спора при реализации своих прав не учитывают все фактические обстоятельства и не учитывают возможный вред для интересов друг друга. Обращено внимание, что разнообразие процессуальных прав в гражданском и хозяйственном судопроизводстве порождает соответствующее количество видов злоупотреблений ими со стороны участников дела.
Some aspects of the abuse of rights in civil and economic proceedings
Keywords: зловживання правом; процесуальні права; реалізація суб’єктивного права; цивільне судочинство; господарське судочинство; судова практика; види зловживання процесуальними правами; abuse of right; procedural rights; exercise of subjective righ; civil justice; economic justice; judicial practice; types of abuse of procedural rights; злоупотребление правом; процессуальные права; реализация субъективного права; гражданское судопроизводство; хозяйственное судопроизводство; судебная практика; виды злоупотребления процессуальными правами